The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmars.2021.665716
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Prediction in Abundance Variation of Atlantic Cod via Long Short-Term Memory With Periodicity, Time–Frequency Co-movement, and Lead-Lag Effect Across Sea Surface Temperature, Sea Surface Salinity, Catches, and Prey Biomass From 1919 to 2016

Abstract: The population of Atlantic cod significantly contributes to the prosperity of fishery production in the world. In this paper, we quantitatively investigate the global abundance variation in Atlantic cod from 1919 to 2016, in favor of spatiotemporal interactions over manifold impact factors at local observation sites, and propose to explore the predictive mechanism with the help of its periodicity, time–frequency co-movement, and lead-lag effects, via long short-term memory (LSTM). We first integrate evidences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…In most fish species, SSS changes determine egg fertilization, incubation, yolk sac resorption, early embryogenesis, and larval growth, according to Boeuf and Payan [86]. Nian et al [87] found that increasing SSS and warming SST directly led to a decline in Atlantic cod abundance from 1919 to 2016. As a result, the fishermen in the zone demand greater information and explanation about SSS changes and their implications.…”
Section: Discussionmentioning
confidence: 99%
“…In most fish species, SSS changes determine egg fertilization, incubation, yolk sac resorption, early embryogenesis, and larval growth, according to Boeuf and Payan [86]. Nian et al [87] found that increasing SSS and warming SST directly led to a decline in Atlantic cod abundance from 1919 to 2016. As a result, the fishermen in the zone demand greater information and explanation about SSS changes and their implications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning (ML), has become one of the most powerful tools in the field of multivariate multi-step time series prediction (Hochreiter and Schmidhuber, 1997;Geurts et al, 2006;Sapankevych and Sankar, 2009;Box et al, 2015;Hu and Zheng, 2020;Nian et al, 2021c). Deep learning could be regarded as one of the hottest topics in the context, and all kinds of most emerging and advanced algorithms have been put forward and made progresses (Hinton and Salakhutdinov, 2006;Krizhevsky et al, 2012;Goodfellow et al, 2014;He et al, 2016;Huang et al, 2017;Wan et al, 2019), such as Recurrent Neural Network (RNN) (Elman, 1990;Lipton et al, 2015;Braakmann-Folgmann et al, 2017;Qin et al, 2017) and Long Short Term Memory (LSTM) (Kalchbrenner et al, 2015;Shi et al, 2015;Greff et al, 2016;Zhang et al, 2017;Shi and Yeung, 2018;Wang et al, 2021;Gangopadhyay et al, 2021;Nian et al, 2021b). We expect to establish a comprehensive predictive model of mesoscale eddy trajectories toward meridional ridges on a global scale in the future, coupling with the topographic effects, via deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…The development of remote sensed technology ensures the wide coverage, high accuracy, and high accessibility to the data of sea surface temperature (SST) 15 . As an important indicator of sea water temperature, the data of SST has been well used to predict the resource distribution of various marine organisms, including Thunnus albacares 16 , Dosidicus gigas 17 , and Gadus morhua 18 . Since aquaculture is primarily conducted in coastal areas, it is directly affected by the local sea surface temperature.…”
Section: Introductionmentioning
confidence: 99%